FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERSIHAN LINGKUNGAN PANTAI INDAH KELURAHAN KOTO JAYA KECAMATAN KOTA MUKOMUKO - Muliana, Indra; Rianto, Slamet; U, Iswandi (STKIP PGRI Sumbar, 2013)
One of the problems of waste is sufficiently complicated that there are in the neighborhood along the beautiful coast, in addition to a relatively large number and behavior of people who are less concerned about the cleanliness of the environment is another factor that led to the problems contained in beach Indah Koto Jaya village. This study aims to factors affecting environmental hygiene along the beach Indah Koto Jaya village Mukomuko.The study was descriptive correlational . The population in this study overall picturesque coastal village communities Koto Jaya Mukomuko districts, amounting to 398 families . Samples were taken with a sampling technique with poroporsi probaliti 25% so that the sample bejumlah 100 householdsThe research found that: 1 ) There is a relationship with the education level of environmental hygiene in beach Indah Koto Jaya village of District City Mukomuko. for t > t table ( 5.154 > 1.662 ) , the strength of the relationship being ( r = 0.462 ) and a small contribution ( 21.3 % ) , ( 2 ) There is a relationship with a waste disposal facility environmental hygiene in beach Indah Koto Jaya village of District City Mukomuko because t count > t table ( 2.326 > 1.662 ), the magnitude of the low relationship ( r = 0.229 ) and the amount of the contribution is very small ( 5.2 % ), ( 3 ) There was no relationship of family members with a healthy environment along beach Indah Koto Jaya village of District City Mukomuko for t < t table ( -0.056 > 1.662 ), the relationship is very low ( r = 0.062 ), and a very small contribution ( 0.04% ) and ( 4 ) There is a correlation between education , waste disposal facilities and the number of family members together together with environmental hygiene in Koto village along beach Indah Koto Jaya village of District City Mukomuko because Fhitung > F table ( 10.794 > 2.751 ) , strength . The third relationship with the cleanliness of the environment variable in Koto village along beach Indah Koto Jaya village of District City Mukomuko including medium category ( r = 0.502 ) and amount of the contribution is small ( 25.2 % ).